Digital Storytelling in Cultural Tourism: A Sustainable Communication Approach at the Lasem Heritage Foundation - Intan Putri Cahyani; Puri Bestari Mardani; Yuliani Widianingsih (Research Synergy Foundation, 2023)
Responsible cultural tourism requires a sustainable approach that includes preserving cultural values while promoting economic and environmental sustainability. This study examines why the Lasem Heritage Foundation chose digital storytelling as a form of sustainable communication for managing cultural tourism and how it aligns with sustainable communication principles. Using a case study approach and qualitative methods, data were collected through interviews, observation, and literature review. Findings indicate that digital storytelling is an effective approach to managing cultural tourism for the Lasem Heritage Foundation, as it provides lasting impact and message amplification. Their Instagram and Website with